Congenital tuberculosis in a neonate following in vitro fertilization-embryo transfer: A case report - Zhuang, Guiying; Yang, Linzhi; Qu, Liuhong; Liu, Weiqi; Zhu, Huanjin (Frontiers in Pediatrics, 2022)
Background: Congenital tuberculosis is becoming increasingly common, but congenital tuberculosis infection in neonates following in vitro fertilization and embryo transfer (IVF-ET) has been rarely reported; a diagnosis of congenital tuberculosis is often delayed due to the non-specificity of maternal IVF treatments and clinical manifestations during pregnancy—particularly in low-birth-weight preterm infants. Case presentation: We herein report a case of congenital tuberculosis. The infant was born at 27+5 weeks of gestation and was admitted to the hospital due to hypopnea after birth. Due to a poor response to treatment, we conducted pathogenic microorganism metagenomic analysis to assess the nucleotide sequences within the Mycobacterium tuberculosis complex. After collecting sputum, the strains from the tuberculosis analysis were isolated and confirmed. From a detailed examination of the mother and in accordance with the child's congenital tuberculosis, we confirmed the diagnosis of pelvic tuberculosis. Conclusion: IVF treatment and pregnancy can exacerbate latent tuberculosis, especially in women from a family with a history of tuberculosis infections. We posit that the optimal way to prevent neonatal congenital tuberculosis in IVF-ET is to procure a detailed maternal medical or family history and to identify and treat maternal tuberculosis during IVF treatment.